2014
DOI: 10.1155/2014/924184
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Genetic Screening of Electromagnetic Hypersensitive Subjects as a Feasible Tool for Diagnostics and Intervention

Abstract: Growing numbers of “electromagnetic hypersensitive” (EHS) people worldwide self-report severely disabling, multiorgan, non-specific symptoms when exposed to low-dose electromagnetic radiations, often associated with symptoms of multiple chemical sensitivity (MCS) and/or other environmental “sensitivity-related illnesses” (SRI). This cluster of chronic inflammatory disorders still lacks validated pathogenetic mechanism, diagnostic biomarkers, and management guidelines. We hypothesized that SRI, not being merely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 49 publications
5
30
2
3
Order By: Relevance
“…In the last decade, literature data provided evidence for the association of MCS with increased oxidative/nitrosative stress and inflammation [9][10][11][12][13][14], likely resulting from defects in xenobiotic metabolism and antioxidant enzyme defenses [26]. A chronic imbalance in redox homeostasis promotes the development of inflammation mainly through the dysregulation of immune response cells and the activation of pro-inflammatory transcription factors [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, literature data provided evidence for the association of MCS with increased oxidative/nitrosative stress and inflammation [9][10][11][12][13][14], likely resulting from defects in xenobiotic metabolism and antioxidant enzyme defenses [26]. A chronic imbalance in redox homeostasis promotes the development of inflammation mainly through the dysregulation of immune response cells and the activation of pro-inflammatory transcription factors [27].…”
Section: Discussionmentioning
confidence: 99%
“…To date the proposed etiopathogenetic mechanism involves an aberrant activation of the vicious cycle N-methyl-d-aspartate (NMDA)-nitric oxide/peroxynitrite triggered by various chemical agents, that ultimately lead to oxidative stress and activation of pro-inflammatory transcription factors [8]. Indeed, dramatically increased levels of reactive oxygen and nitrogen species (ROS, RNS), as well as pro-inflammatory cytokines and the presence of autoimmune antibodies, have been reported in MCS patients compared with healthy subjects [9][10][11][12][13][14]. Moreover, a link has been suggested between MCS and inherited or acquired defects in genes coding for enzymes involved in xenobiotic metabolism phase I and II, antioxidant defense, lipid metabolism and one-carbon pathway [11,12,[15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, RF-EMF exposure could induce various neurological changes. Information of phenotypes or symptoms following EMF exposure is still lacking even though some of studies have been reported with respect to electromagnetic hypersensitivity following EMF exposure3233.…”
mentioning
confidence: 99%
“…A study by De Luca et al, in 2014 on 153 EHS and 132 controls showed metabolic pro-oxidant/pro-inflammatory alterations in EHS like decreased erythrocyte glutathione S-transferase (GST) activity, decreased reduced glutathione (GSH) levels, increased erythrocyte glutathione peroxidase (GPX) activity, an increased ratio of oxidizedCoQ10/total-CoQ10 in plasma, and a 10-fold increased risk associated with EHS for the detoxifying enzymes glutathione S transferase haplotype (null) GSTT1+(null) GSTM1 variants (242).…”
Section: Possible Mechanism Of Ehsmentioning
confidence: 99%